(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article examines the theoretical and methodological foundations of using interactive teaching strategies to develop university students’ speaking competence. Speaking competence is interpreted as an integrated combination of grammatical knowledge, vocabulary, fluency, pronunciation, pragmatic appropriateness, and the ability to respond flexibly to different communicative situations. The pedagogical potential of cooperative learning, role-play, discussion, problem-solving, information-gap activities, project work, and digital storytelling is analysed. Particular attention is paid to the organisation of interactive lessons, the distribution of communicative roles, the creation of psychologically supportive learning environments, and the assessment of oral performance. The article argues that systematic interaction transforms students from passive recipients of information into independent, reflective, and socially responsible communicators.